Exosomes Derived From Human Gingival Mesenchymal Stem Cells Attenuate the Inflammatory Response in Periodontal Ligament Stem Cells - Sun, Jiayao; Wang, Zhiguo; Liu, Peng; Hu, Yingzhe; Li, Tingting; Yang, Jianbo; Gao, Pengyu; Xu, Quanchen (Frontiers in Chemistry, 2022)
This study aimed to explore the effects of exosomes derived from human gingival mesenchymal stem cells (GMSC-Exo) on the inflammatory response of periodontal ligament stem cells (PDLSCs) in an inflammatory microenvironment in order to restore the regenerative potential of PDLSCs, which promotes periodontal tissue regeneration in patients with periodontitis. Periodontitis is a chronic infectious disease characterized by periodontal tissue inflammation and alveolar bone destruction. PDLSCs are regarded as promising seed cells for restoring periodontal tissue defects because of their ability to regenerate cementum/PDL-like tissue and alveolar bone. However, PDLSCs in the inflammatory environment show significantly attenuated regenerative potential. GMSC-Exo have been reported to have anti-inflammatory and immunosuppressive properties. In this study, we investigated the effects of GMSC-Exo on the inflammatory response of PDLSCs induced by lipopolysaccharides (LPS). LPS was used to simulate the inflammatory microenvironment of periodontitis in vitro. GMSC-Exo were extracted from the culture supernatant of GMSCs by ultracentrifugation. We found that GMSC-Exo attenuated the inflammatory response of PDLSCs induced by LPS. Furthermore, compared to treatment with LPS, treatment with GMSC-Exo attenuated the expression of NF-κB signaling and Wnt5a in LPS-induced PDLSCs. In conclusion, we confirmed that GMSC-Exo could suppress the inflammatory response of PDLSCs by regulating the expression of NF-κB signaling and Wnt5a, which paves the way for the establishment of a therapeutic approach for periodontitis.